Interactive design galleries: A general approach to interacting with design alternatives. (September 2017) - Woodbury, Robert; Mohiuddin, Arefin; Cichy, Mark; Mueller, Volker
Abstract : Designers work by exploring alternatives. While extant parametric modelers theoretically define alternatives, their interfaces generally provide access to designs serially. Our goal is to change this near-universal feature of parametric interfaces to support exploration using multiple alternatives. We built a prototype gallery system on a web browser that supports saving alternatives from three graph-based parametric modeling tools. Users can retrieve alternatives from the gallery, share them with others, and combine them to generate more alternatives. We evaluated this system qualitatively in a workshop with ten expert designers working on their own design problems. We learnt that users prefer the gallery to their accustomed workarounds. The study produced several directions for new user interface designs. Highlights: We outline a representation for parametric design alternatives and demonstrate key representational properties. The Cartesian product of a collection of alternatives produces a larger collection of related alternatives. We built a modeler-independent, web-based gallery system supporting alternatives. A user study showed that designers find the gallery useful and revealed new patterns of use with the gallery tool. From the user study we derive several new directions for the gallery system and its interface.